2015
DOI: 10.1037/xge0000050
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the efficacy of acceptance-based behavioral therapy for academic procrastination.

Abstract: Procrastination among college students is both prevalent and troublesome, harming both academic performance and physical health. Unfortunately, no "gold standard" intervention exists. Research suggests that psychological inflexibility may drive procrastination. Accordingly, interventions using acceptance and mindfulness methods to increase psychological flexibility may decrease procrastination. This study compared time management and acceptance-based behavioral interventions. College students' predictions of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 49 publications
5
67
0
7
Order By: Relevance
“…One of the most significant barriers to the development of effective interventions for academic procrastination is the lack of understanding of the constructs responsible for causing and maintaining the behavior (Glick & Orsillo, 2015). While we are not in a position to delineate effective interventions for academic procrastination behavior in Asian international students, we believe that this research can be used to provide some general guidance.…”
Section: Discussionmentioning
confidence: 96%
“…One of the most significant barriers to the development of effective interventions for academic procrastination is the lack of understanding of the constructs responsible for causing and maintaining the behavior (Glick & Orsillo, 2015). While we are not in a position to delineate effective interventions for academic procrastination behavior in Asian international students, we believe that this research can be used to provide some general guidance.…”
Section: Discussionmentioning
confidence: 96%
“…Lately, Gieselmann and Pietrowsky (2016), Glick and Orsillo (2015), and Hafner et al (2014) have all conducted randomized controlled trials, administering either implementation intentions, time management, or acceptance-based behavioral interventions. Although indicating some benefits, the treatment durations were very short.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies evaluated a 10-week guided Internet-delivered exposure and mindfulnessbased intervention "inspired by the third wave of CBT" (Ljótsson, Andersson, et al, 2011, p. 4;Ljótsson et al, 2010;. Glick and Orsillo (2015) investigated the efficacy of Internet-delivered acceptance-based behavior therapy. CFT and CMT informed the remaining unguided Internet-delivered treatments (Kelly & Carter, 2015;Shapira & Mongrain, 2010).…”
Section: E F F I C a C Y A N D A C C E P T A B I L I T Y O F T H I R mentioning
confidence: 99%
“…Participants rated the treatments as satisfactory (Trompetter et al, 2015;Lappalainen et al, 2014Lappalainen et al, , 2015, enjoyable (Glick & Orsillo, 2015), useful (Kristjánsdóttir et al, 2013), and helpful (Cukrowicz & Joiner, 2007), as measured by the Client Satisfaction Questionnaire (Attkisson & Zwick, 1982), visual analogue scales, and brief questionnaires, respectively. Four studies administered the Credibility/Expectancy Questionnaire (Borkovec & Nau, 1972;Devilly & Borkovec, 2000) and ratings indicated that participants perceived the third-wave eHealth treatments as credible (Kelly & Carter, 2015;Ljótsson et al, 2010;Ly et al, 2014).…”
Section: Secondary Outcomesmentioning
confidence: 99%